Paradigm Shift in Corruption Punishment: From Imprisonment to State Loss Recovery in the Makassar District Court Decision - Muhammad Djaelani Prasetya (Law Research Review Quarterly, 2026)
Corruption as a crime of office, develops towards economic crime that causes state financial losses and requires efforts to recover state assets. These developments affect the practice of criminalizing corruption in Indonesia, especially in the relationship between the public prosecutor's demands and the judge's decision. This study aims to analyze the paradigm shift in corruption punishment in the 2024 Makassar District Court decision through imprisonment, fines, and compensation. This study uses a type of empirical legal research with a socio-legal approach. The research data sources consist of the 2024 Makassar District Court corruption verdict and various legal literature. The results of the study show that prison sentences are still prioritized. However, the practice shows a paradigm shift in punishment through the strengthening of criminal fines and compensation as a means of recovering state losses. In some cases, prison sentences were lowered compared to the Prosecutor's demands, but the substitute money was maintained and even increased. This finding indicates that the criminalization of corruption in Indonesia is moving from prison-oriented punishment to recovery-oriented punishment. However, the recovery of state losses cannot remove prison sentences because the deterrence function is still necessary in the eradication of corruption.